Design of Single Switch Resonant Converter with Parallel Load Resonant for Colour Removal in Palm Oil Mill Effluent - Mochammad Facta; Karnoto .; Zainal Salam; Zolkafle Buntat (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Indonesia has palm oil harvesting as the most important agriculture crop. Unfortunately, this agricultural activity delivers a large amount of by product, known as palm oil mills effluent (POME). The treatment using membrane bioreactor has successfully removed the heavy organic component of POME but it left water in colour. This paper proposed the use of a single switch resonant converter with parallel load resoant with dielectric barrier discharge ozonizer to remove colour of treated POME. The ozonizer chamber was made from a planar metal dielectric barrier discharge construction. A single switch resonant converter as power supply to the chamber was designed and it is based on resonance principle. This circuit converted a direct current low voltage input into high frequency and sinusoidal voltage output. The high voltage created micro electrical discharges inside chamber to generate ozone from oxygen molecules. At atmospheric pressure and ambient temperature, the ozonizer deliver up to 2300 ppm ozone gas. The ozone gas was injected into the treated POME for several duration of time. The results of experiment showed that the treated POME water has successfully changed in colour from 100 mg/l Pt.Co into 20 mg/l Pt.Co or lower. As the time of treatment is increased then the colour abatement was below 15 mL/l Pt.Co.Keywords—